The Influence of Global Mindset, Individual Characteristics and Job Characteristics on Employee Work Performance with Organizational Commitment as an Intervening Variable at Company: Pengaruh Global Mindset, Karakteristik Individu dan Karakteristik Pekerjaan terhadap Prestasi Kerja Karyawan dengan Komitmen Organisasi sebagai Variabel Intervening di Perusahaan - Ningrati, Nur Rahayu; Sumartik (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the Global Mindset, Individual Characteristics, and Individual Characteristics on Employee Work Performance with Intervening Variable Organizational Commitment PT. PG Candi Baru. This research is a type of quantitative research with hypothesis testing. The sample used in this study were 50 employees of PT. PG Candi Baru. The analytical tool used in this research is partial least square (PLS). The results of this study prove that Global Mindset has an effect on Organizational Commitment, Individual Characteristics has an effect on Organizational Commitment, Individual Characteristics has an effect on Organizational Commitment, Global Mindset has an effect on work performance, Individual Characteristics has an effect on work performance, Individual Characteristics has an effect on work performance, Organizational Commitment affects on job performance, Global Mindset affects work performance mediated by Organizational Commitment, Individual Characteristics affects work performance mediated by Organizational Commitment, Individual Characteristics affects work performance mediated by Organizational Commitment.